2012
DOI: 10.5539/elt.v5n7p110
|View full text |Cite
|
Sign up to set email alerts
|

Do Language Proficiency Levels Correspond to Language Learning Strategy Adoption?

Abstract: The primary focus of research on employment of language learning strategies has been on identification of adoption of different learning strategies. However, the relationship between language learning strategies and proficiency levels was ignored in previous research. The present study was undertaken to find out whether there are any relationship between the employment of different strategies and learners' levels of language proficiency. To this end, initially, a simulated TOEFL test (Bailey, R. F., Seetharama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 41 publications
5
19
0
Order By: Relevance
“…This means that successful language learners demonstrated greater consistency in applying more effective strategies. The findings of the present study are in line with Gharbavi and Mousavi (2012) and Pei-Shi (2012) which showed that the higher the level that learners are at, the greater the number of strategies they will apply. Oxford (1990) also claims that all language learners" use learning strategies, but more successful learners use them more consciously, more appropriately, more purposefully and more frequently.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This means that successful language learners demonstrated greater consistency in applying more effective strategies. The findings of the present study are in line with Gharbavi and Mousavi (2012) and Pei-Shi (2012) which showed that the higher the level that learners are at, the greater the number of strategies they will apply. Oxford (1990) also claims that all language learners" use learning strategies, but more successful learners use them more consciously, more appropriately, more purposefully and more frequently.…”
Section: Discussionsupporting
confidence: 92%
“…Studies by O" Malley and Chamot (1989) and Gu and Johnson (1996) (cited in Cabaysa & Baetiong, 2010 p. 24) also prove that successful learners made use of combinations of strategies. This is supported by a study conducted by Gharbavi and Mousavi (2012) that shows the higher the level the learners are at, the greater the number of strategies they use.…”
Section: Introductionmentioning
confidence: 76%
“…Many previous studies agree that learning strategy use differs depending on the students' level of language proficiency. They have found that students of advanced-level proficiency use overall strategies more often than students with lower-level proficiency (e.g., Baker & Boonkit, 2004;Gharbavi & Seyyed, 2012). Considering the low level of English proficiency of the participants in this study, the result of low medium use of learning strategies is consistent with these previous findings.…”
Section: Discussionsupporting
confidence: 82%
“…Although many related studies have been conducted (e.g., Gharbavi & Mousavi, 2012;Lee, 2003;Pazhakh, 2006), few researchers have investigated the relationship between SRLSs and language proficiency. However, these findings are in line with Mirhassani's et al (2007) research findings that showed the positive relationship between these two variables.…”
Section: Discussionmentioning
confidence: 99%